ANALISIS KINERJA SIMPANG TAK BERSINYAL PADA BUNDARAN MENGGUNAKAN SOFTWARE PTV VISSIM 9.0 DENGAN METODE MKJI 1997 (Studi kasus Bundaran Cunda Jalan Merdeka Timur, Jalan Medan-Banda Aceh) - Widari, Lis Ayu; Olanda, T.M.Riski; Chandra, Yovi; Maryana, Maryana; Zuraida, Zuraida (Universitas Malikussaleh, 2023)
Congestion and delays often occur in several sections and intersections of Lhokseumawe City roads. Currently the City of Lhokseumawe has implemented a regional traffic control system at several intersections, but at the Cunda roundabout, Jalan Merdeka Timur (direction out of town), Jalan Medan - Banda Aceh (National Cross Road), which does not yet have traffic control or signs. other warnings causing traffic jams. This research was conducted at the Cunda Roundabout in Lhokseumawe City with the aim of seeing the condition and performance of the roundabout. The data needed in this study include vehicle volume characteristics, road geometry and other secondary data. The method used for this research is the 1997 Indonesian Road Capacity Manual and a 3-dimensional simulation based on Vissim. The results of the analysis show that the peak hour on Monday at 17.00-18.00 WIB is 7616 vehicles/hour with a degree of saturation of 1.104, based on MKJI the DS value for roundabouts < 0.75, the roundabout performance is no longer able to accommodate traffic loads and long queues. , especially from Jalan Merdeka Timur and Jalan Medan - Banda Aceh. After re-planning the roundabout from unsignaled to signaled by adding traffic light settings, so that a better degree of saturation is obtained, which is 0.78. The obtained value of the degree of saturation indicates that the intersection is not close to saturation, and the performance is starting to stabilize with a value of DS is still smaller than 0.85 (the 1997 MKJI requirement for signalized intersections), so the roundabout performance becomes more effective.